Exploring the Efficacy of a Mindfulness Program for Boys With Attention-Deficit Hyperactivity Disorder and Oppositional Defiant Disorder. Issue 11 (September 2021) - Muratori, Pietro; Conversano, Ciro; Levantini, Valentina; Masi, Gabriele; Milone, Annarita; Villani, Silvia; Bögels, Susan; Gemignani, Angelo
Objective: This study was the first attempt to explore the efficacy of a mindfulness protocol for children with attention-deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD), and their parents.Method: Fifty male children with ADHD and ODD diagnosis, aged 8 to 12, were randomly assigned to the mindfulness intervention ( n = 25) or the wait-list ( n = 25) group. Outcome measures included children, parents', and teachers' reports and objective measures of attention.Results: Children from the intervention group had a greater reduction in hyperactive behaviors in the school context (effect size [ES] = 0.59) and a greater improvement in visual sustained attention (ES = 0.77) and in Avoidance and Fusion Questionnaire scores (ES = 0.43) than those in the wait-list control group. No significant effect of the intervention on aggressive behaviors was revealed.Conclusion: A mindfulness intervention for children and their parents showed partial beneficial effects in children with ADHD + ODD.